If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(8 + 6x) = 32 + 8x (8 * -4 + 6x * -4) = 32 + 8x (-32 + -24x) = 32 + 8x Solving -32 + -24x = 32 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -32 + -24x + -8x = 32 + 8x + -8x Combine like terms: -24x + -8x = -32x -32 + -32x = 32 + 8x + -8x Combine like terms: 8x + -8x = 0 -32 + -32x = 32 + 0 -32 + -32x = 32 Add '32' to each side of the equation. -32 + 32 + -32x = 32 + 32 Combine like terms: -32 + 32 = 0 0 + -32x = 32 + 32 -32x = 32 + 32 Combine like terms: 32 + 32 = 64 -32x = 64 Divide each side by '-32'. x = -2 Simplifying x = -2
| 4t+9=-7m+18 | | 2/8=7 | | f(3x)=3x^3-18x^2+3 | | 3/8x-6 | | 2x+26y=14 | | -1=x/-6 | | 16-x=x+6 | | 3(4u-4)=5[-2u+2(-u-3)] | | 4yx+3yx= | | -6*(1-4*x)^1/2=-30 | | -2(7x+4)=-120 | | y=5/2(4)-2 | | 4+5(4k-4)=104 | | -3b-3b=12 | | 4y+3x=11 | | -13y-26=7y+22 | | 8x+20=5x+35 | | 3x-7y+6z=5 | | X^8=1/12 | | 16/5x=1/10 | | x-5y=-2 | | 9=2w+5 | | -8n-3=-27 | | 3(3x-3)-28=4x-2 | | 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x |